Performance of Alternative Estimation Procedures of the Implied Equity Duration in a Small Stock Market - Fullana, Olga; Toscano, David (Sustainability, 2020)
This paper is focused on the measurement of interest rate risk of nonfinancial firms. The measurement is the initial step in the risk management, which, in the context of financial risks, it is expected to lead to better levels of enterprises' financial sustainability. Concretely, we checked the performance of alternative estimation procedures of the implied equity duration as a measure of the exposure to interest rate risk of firms listed on a small stock market. Previous evidence in the US stock market shows that when the implied equity duration is computed using industry-specific parameters instead of market parameters, significant differences arise in their absolute and relative values and even in their ranking. In this paper, we checked the robustness of these results when we moved to a smaller stock market. To do so, we replicated previous analyses carried out in the Spanish stock market but using alternative estimation procedures. We conclude that significant differences arise in the implied equity duration estimations when we consider industry-specific parameters instead of market parameters. This finding in a small stock market is in line with previous evidence found for the US stock market.
Keywords: financial sustainability; financial risk; interest rate risk; stock duration; Scopus; JCR